Urban green spaces activities: A preparatory groundwork for a safety management system. (February 2016) - Bortolini, Lucia; Cividino, Sirio R.S.; Gubiani, Rino; Cecchini, Massimo; Delfanti, Lavinia M.P.; Colantoni, Andrea
Abstract: Introduction: Urban green spaces works and maintenance are high-risk activities and usually represent possible sources of injuries. The management issues are complex and strongly influenced by companies' policies in terms of safety management and human factor. A high number of tasks—including protecting public health and safety and safe working procedures—need to be faced by professional arborists or gardeners. Method: The present paper provides a preparatory groundwork for modeling and describing the real risk levels during the abovementioned activities. The methodology represents a useful tool for decision making both for group leaders and safety coordinators. This goal is reached by collecting data emerging from several workplaces located in North East Italy regarding the frequency and severity of injuries. Results: The preliminary results point out that the most frequent injuries in green maintenance activities are represented by cuts, contusions, and ocular lesions, but none of them have lead to particularly serious consequences for the operators; indeed, the high levels of severity are related to traumas, fractures, and acute lumbar herniated discs. The riskiest activities are related to pruning, especially using mobile elevating work platforms, and grass cutting, especially when operated in escarpments and banks. Workers' behavior and companies' safety policies are key elements for a correct safety management system. Highlights: The activities in green urban areas have been studied. Modelling paradigms in risk management. The management issues are complex and strongly influenced by companies' policies in terms of safety management and human factor. A high number of tasks—including protecting public health and safety and safe working procedures—need to be faced by professional arborists or gardeners